Sensibilidade e especificidade no diagnostico da hipertensão a partir de diferentes protocolos de aferição da pressão arterial - Nascimento, Larissa Rangel (2010)
Introduction: The measurement of blood pressure (BP) out of the doctor's office, following properly the pre-established protocols, presents several advantages over the traditionally used in the clinic for the diagnosis of hypertension. Objective: To evaluate the sensitivity and specificity of three different protocols of blood pressure measurement for the diagnosis of hypertension. Methodology: Cross-sectional study non-probabilistic sample of 250 employees from a public institution of higher education. Participants had their BP measured by three methods: clinical measure (MCPA), self-measurement (AMPA) and 24 hours ambulatory measurement (ABPM). Anthropometric and socio-demographic data were also collected. The methods were compared and analyzed in relation to MAP (gold standard) and checked possible association with other variables. Results: The AMPA showed higher sensitivity (S = 84% CI 75-93) and overall accuracy (AG = 0.817, p <0.001) in the diagnosis of hypertension that MCPA (S = 79% CI = 73-86 and AG 0.815, p <0.001). Despite the strong correlation with the method of ABPM during wakefulness (r = 0.843, p = 0.000), the AMPA did not show good agreement with the above method to measure systolic (bias = 5.82, 95% CI = 4.49 -7.15). Conclusion: AMPA, can be used to aid in the diagnosis of hypertension, with respect to suspicion of this injury but can not replace the MCPA, which is still the most reliable method.